Occurrence and State Approaches fer Addressing Cyanotoxins in US Drinking Water. Issue 2 (1st February 2017) - Henrie, Tarrah; Plummer, Sarah; Roberson, J. Alan
Abstract : CYANOTOXINS ARE BECOMING A MORE IMPORTANT ISSUE FOR WATER SYSTEMS SINCE THE US ENVIRONMENTAL PROTECTION AGENCY RELEASED HEALTH ADVISORIES (HAs) AND RECOMMENDATIONS FOR SYSTEMS' RESPONSES IN 2015. THIS ARTICLE SUMMARIZES HOW STATE PRIMACY AGENCIES HAVE RESPONDED TO THE HAs.